Eco-Labeling Perspectives amongst Malaysian Consumers - Nik Abdul Rashid, Nik Ramli; Jusoff, Kamaruzaman; Mohamed Kassim, Kamsol (2009)
This study explores the Malaysian consumers trust of an eco-label and the influence it has in their choice for the corresponding environment friendly product. Taking into consideration the infancy stage of the Malaysia green marketing initiative, traditional approach to evaluating local consumer receptiveness to the eco-label might not be suitable. This paper approaches the introduction of eco-label with two perspectives in mind. Firstly, while earlier studies from the western scholars use eco-label as a part of the augmented product, this study introduces eco-label as a separate moderating variable. Secondly, the choice of employees working in ISO14001 certified organizations as the population explore a potentially conducive place to initiate a systematic effort in developing a green consumer community. The result is very encouraging. This study has shown that, with some exposure to environmental related experiences Malaysian consumer would indeed react positively to the eco-label. In fact, for situation that requires them to consider environmental aspects of a product that they wish to purchase, the eco-label will definitely be the crucial factor that will push them to make the right purchase choice.